PENINGKATAN HASIL BELAJAR TEMA DAERAH TEMPAT TINGGALKU MELALUI METODE PERMAINAN BINGO PADA SISWA KELAS IV SDN 007 SUNGAI PINANG TAHUN PEMBELAJARAN 2018/2019 - Oktaviani, Siska; Ikhsan, Muhammad; Firdausetia, Nur Magfira (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
This study intended to improve students learning outcomes on force and motion material using the bingo game. This research was Classroom Action Research (CAR) conducted in three cycles. The subjects of the study were 26 children, consisting of 16 male students and 10 female students. Data collection techniques with observation and documentation and test learning outcomes.The results showed in the first cycle with an average value of 66, the second cycle an average value of 80.76, and the third cycle an average value of 90.38. The level of completeness in the first cycle was 38.46%, in the second cycle was 76.92%, and the third cycle increased to 92.30%. Thus, the level of completeness from cycle I to cycle II rose 30.77%, and cycle II to cycle III growth to 22.98%. Using the bingo game can increase student activity from cycle I to cycle III. In cycle I, there are aspects of attention 61.5%, activeness 38.4% and participation 46.1% have increased in cycle II on aspects of attention 73%, activeness 57.6%, 61.5% participation and increased in cycle III, namely in the aspect of attention to 92.3% activeness to 84.6% and participation aspects to 80.75%.In the assessment, there are two namely the spiritual attitude and social attitude. There are 3 aspects of spiritual attitude, namely thankful behavior, praying before and after doing activities, and saying hello when entering and leaving the room. And there are 5 aspects of social attitude, namely discipline, care, confidence, courtesy, and responsibility. It was seen that from cycle I to cycle III has increased in both good and very good categories. In the first cycle skills assessment with a percentage of 42.30%, cycle II with a percentage of 73.07%, and cycle III with a percentage of 92.30.